2012
DOI: 10.1007/s00167-012-1944-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the minimally invasive and standard medial parapatellar approaches for primary total knee arthroplasty

Abstract: Therapeutic study, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
18
1
2
Order By: Relevance
“…In contrast to these positive findings, some recently published and well-designed studies [12][13][14][15][16] and 2 meta-analyses 17,18 have indicated that minimally invasive total knee arthroplasty could also have important shortcomings, such as prolonged operative time, an increased number of wound complications, and more malpositioning of the prosthesis. However, these randomized clinical trials had relatively short-term follow-up and had neither patient-reported outcomes nor radiographic evaluations.…”
mentioning
confidence: 99%
“…In contrast to these positive findings, some recently published and well-designed studies [12][13][14][15][16] and 2 meta-analyses 17,18 have indicated that minimally invasive total knee arthroplasty could also have important shortcomings, such as prolonged operative time, an increased number of wound complications, and more malpositioning of the prosthesis. However, these randomized clinical trials had relatively short-term follow-up and had neither patient-reported outcomes nor radiographic evaluations.…”
mentioning
confidence: 99%
“…However, to date these interventions have not resulted in clear improvements in patient outcomes one year or more after TKA [23][24][25][26]. Continuing to improve the quality and consistency of TKA via advances in surgical technique and instrumentation, perioperative pain control, and/or implant design is necessary, but the clinical benefits of the aforementioned interventions may be masked by concomitant non-orthopedic issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, results are still not conclusive. In general, MIS approaches appear to give better earlier flexion and/or range of motion [5258] although not for all MIS approaches [52, 53]. The majority showed earlier straight leg raise [52, 53, 55] but not all [54].…”
Section: Compare Conventional Surgical Technique Vs Mismentioning
confidence: 99%
“…MIS appears to improve immediate post-operative pain scores [52, 54] and early KSS [52, 53, 57] although one analysis found no difference in KSS [54]. Based on the current meta-analyses [5258] there are conflicting results for blood loss, LoS, wound problems and peri-operative complications between MIS and standard approaches, so it is still not easy to draw conclusions. However, two of the most recent meta-analyses have shown no clinical advantages for the quadriceps sparing approach over the medial parapatellar but an increased risk of malalignment and malposition [59, 60].…”
Section: Compare Conventional Surgical Technique Vs Mismentioning
confidence: 99%